1986
DOI: 10.1128/jb.165.3.787-795.1986
|View full text |Cite
|
Sign up to set email alerts
|

Lateral diffusion of proteins in the periplasm of Escherichia coli

Abstract: We have introduced biologically active, fluorescently labeled maltose-binding protein into the periplasmic space of Escherichia coli and measured its lateral diffusion coefficient by the fluorescence photobleaching recovery method. Diffusion of this protein in the periplasm was found to be surprisingly low (lateral diffusion coefficient, 0.9 x 10-10 cm2 S-1), about 1,000-fold lower than would be expected for diffusion in aqueous medium and almost 100-fold lower than for an equivalent-size protein in the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 57 publications
4
55
2
Order By: Relevance
“…Interestingly, the maltose-binding protein (MBP), which is associated with the chemoreceptor Tar to sense maltose, also exhibits a polar localization (14). In addition, MBP can diffuse laterally in the periplasm (36), and the induction of its synthesis by adding maltose in the medium triggers polar cap formation in E. coli (37). These observations strongly suggest that bacteria detect the nutrient substances at the poles.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the maltose-binding protein (MBP), which is associated with the chemoreceptor Tar to sense maltose, also exhibits a polar localization (14). In addition, MBP can diffuse laterally in the periplasm (36), and the induction of its synthesis by adding maltose in the medium triggers polar cap formation in E. coli (37). These observations strongly suggest that bacteria detect the nutrient substances at the poles.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed possible that labeled proteins might penetrate only into the periplasmic space and that plasmolysis might result in expansion of the periplasm into what are normally cytoplasmic regions of the cell, thus giving the appearance of cytoplasmic labeling. Plasmolyzed cells grossly resembling the triplet distribution have been described (1). We also considered the possibility that the nucleoid might quench fluorescence or otherwise perturb fluorescent emissions emanating from the cell surface or the periplasmic space.…”
Section: Methodsmentioning
confidence: 99%
“…Once in the periplasm, DNA can be transferred into the cell interior by an unknown mechanism; however, proteins do not get past the cytoplasmic membrane in Ca2+-permeabilized cells. These properties have been used to introduce proteins selectively into the periplasmic space (1). As early as 1958, it was observed that the envelope of gram-negative bacteria could be altered in its permeability by brief exposure to EDTA (22,28).…”
mentioning
confidence: 99%
“…By monitoring the kinetics and the extent of movement of fluorescent molecules from the unbleached area into the bleached area, both the percentage of fluorescent molecules that are mobile and their diffusion coefficient can be calculated. This technique has been used successfully to measure the movement of a number of macromolecules in bacteria (21)(22)(23)(24)(25). The fluorescent molecule we chose for use was the GFP from Aequoria victoria, because this protein and its many variants have been used to measure the mobility of soluble proteins in a number of systems (26)(27)(28).…”
mentioning
confidence: 99%